2003
DOI: 10.1111/j.0022-3646.2003.02-142.x
|View full text |Cite
|
Sign up to set email alerts
|

STRUCTURE AND DYNAMICS OF A POPULATION OF PALMARIA PALMATA (RHODOPHYTA) IN NORTHERN SPAIN1

Abstract: Palmaria palmata (Linnaeus) O. Kuntze (Rhodophyta, Palmariaceae) is a seaweed commercially harvested for human consumption. Its population density, size structure, and frond dynamics were investigated from May 1999 to May 2001 at one intertidal locality in the northern coast of Spain, which is within the southern distributional boundary of the species in the eastern Atlantic coasts. The effect of size, age, and the life‐history phase (haploid vs. diploid) on frond growth and mortality were also evaluated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 70 publications
(92 reference statements)
1
19
1
Order By: Relevance
“…The range of growth rates is higher than that recorded from some non-aquaculture field samples, e.g., Faes and Viejo (2003), suggesting the growth rates for P. palmata in the Fundy region significantly exceed those in other regions (e.g., Spain, N. Ireland).…”
Section: Growth Ratesmentioning
confidence: 60%
See 2 more Smart Citations
“…The range of growth rates is higher than that recorded from some non-aquaculture field samples, e.g., Faes and Viejo (2003), suggesting the growth rates for P. palmata in the Fundy region significantly exceed those in other regions (e.g., Spain, N. Ireland).…”
Section: Growth Ratesmentioning
confidence: 60%
“…Environmental factors such as light level, water temperature, average wave height, etc., result in an intrinsic growth rate that is time-dependent (Faes and Viejo 2003). For instance, unpublished data from Northern Ireland showed that Palmaria palmata exhibited dominating growth in the summer months, whereas dominating decay through frond breakage occurred from August to March.…”
Section: Growth Ratementioning
confidence: 99%
See 1 more Smart Citation
“…However, the red seaweed does not survive temperatures above 20°C, limiting its ongrowth in summer and early autumn for some locations. Therefore, during the summer months, at sea, culture of P. palmata is not suitable in all locations, as high temperatures and irradiances can lead to a 'photoinhibition' (bleaching) of Palmaria fronds (Dion & Del epine 1981; Sanderson et al 2012), and a naturally occurring disintegration of frond tips (Mart ınez & Rico 2002;Faes & Viejo 2003;Edwards & Dring 2011). Choosing a site, where it is possible to deepen the nets or droppers if temperature and irradiance become critical, could extend the growth phase and can be beneficial for harvest results.…”
Section: On-growth At Seamentioning
confidence: 99%
“…Despite its cold water affinities, P. palmata occurs in warm temperate waters far south as New Jersey in the western Atlantic Ocean (Taylor 1957) and Portugal in Europe, with localized large populations in northern Spain (Faes and Viejo 2003). Throughout its range P. palmata may be an epiphyte, and it typically occurs in the low intertidal and subtidal zones to depths of about 20 m (Irvine and Guiry 1983, Faes and Viejo 2003, Vadas et al 2004). …”
Section: Introductionmentioning
confidence: 99%